Culture of bovine ovarian follicle wall sections maintained the highly estrogenic profile under basal and chemically defined conditions - Vasconcelos, Rosângela Batista de (2013)
Follicle cultures reproduce in vitro the functional features observed in vivo. In a search for an ideal model, we cultured bovine antral follicle wall sections (FWS) in a serum-free defined medium (DM) known to induce 17β-estradiol (E2) production, and in a nondefined medium (NDM) containing serum. Follicles were sectioned and cultured in NDM or DM for 24 or 48 h. Morphological features were determined by light microscopy. Gene expression of steroidogenic enzymes and follicle-stimulating hormone (FSH) receptor were determined by RT-PCR; progesterone (P4) and E2 concentrations in the media were measured by radioimmunoassay. DM, but not NDM, maintained an FWS morphology in vitro that was similar to fresh tissue. DM also induced an increase in the expression of all steroidogenic enzymes, except FSH receptor, but NDM did not. In both DM and NDM, there was a gradual increase in P4 throughout the culture period; however, P4 concentration was significantly higher in NDM. In both media, E2 concentration was increased at 24 h, followed by a decrease at 48 h. The E2:P4 ratio was higher in DM than in NDM. These results suggest that DM maintains morphological structure, upregulates the expression of steroidogenic enzyme genes, and maintains steroid production with a high E2:P4 ratio in FWS cultures.